Self-Reported Autistic Traits and Stress Level of University Students in China - Jiang Zhen; Low Hui Min (INCLUSIVE EDUCATION, 2023)
In Asian countries such as China, little research has been conducted on autism other than in early childhood, and thus the prevalence and psychosocial outcomes of young people with recognisable high levels of autistic traits remain largely unknown. This study used an online questionnaire format and the survey consisted of two scales, the Autism Spectrum Questionnaire (AQ-28) and the Perceived Stress Scale (PSS). The sample used for the study covered musicology majors, freshmen through seniors to ensure a diverse sample. A total of 111 undergraduate students participated in the survey. Their responses were analysed to examine the relationship between autistic traits and stress. The results of the study showed a positive correlation between autistic traits and stress, indicating that the higher the autistic traits, the higher the stress. Specifically, the social aspect of autistic traits was found to be the most significant predictor of stress. The findings suggest that it makes sense to provide social skills training to young people with high levels of autistic traits in order to improve their socialisation and reduce their stress. The paper also makes recommendations for environmental and social adaptation